The plakin domain of C. elegans VAB-10/plectin acts as a hub in a mechanotransduction pathway to promote morphogenesis - Suman, Shashi Kumar; Daday, Csaba; Gräter, Frauke (Development, 2019)
Mechanical forces can elicit a mechanotransduction response through junction-associated proteins. In contrast to the wealth of knowledge available for focal adhesions and adherens junctions, much less is known about mechanotransduction at hemidesmosomes. Here, we focus on the C. elegans plectin homolog VAB-10A, the only evolutionary conserved hemidesmosome component. In C. elegans, muscle contractions induce a mechanotransduction pathway in the epidermis through hemidesmosomes. We used CRISPR to precisely remove spectrin repeats (SRs) or a partially hidden Src homology 3 (SH3) domain within the VAB-10 plakin domain. Deleting the SH3 or SR8 domains in combination with mutations affecting mechanotransduction, or just the part of SR5 shielding the SH3 domain, induced embryonic elongation arrest because hemidesmosomes collapse. Notably, recruitment of GIT-1, the first mechanotransduction player, requires the SR5 domain and the hemidesmosome transmembrane receptor LET-805. Furthermore, molecular dynamics simulations confirmed that forces acting on VAB-10 could make the central SH3 domain, otherwise in contact with SR4, available for interaction. Collectively, our data strongly indicate that the plakin domain plays a central role in mechanotransduction and raise the possibility that VAB-10/plectin might act as a mechanosensor.
Gesehen am 19.02.2020